Socio-cultural dimensions of retired teachers' lived experiences - Capili, Maria Antonia Crudo; Muega, Maricris B. Acido; Abuso, Julian Elloso 1944-.; Castro, Nestor T.; Manzano, Virgilio U.; Yangco, Rosanelia V. Tablico 1954- (Quezon City College of Education, University of the Philippines Diliman, 2013)
"This study explored the socio-cultural dimensions embedded in the experiences of ten retired teachers. The experiences of the teachers became the basis in constructing the world teachers lived in. To give justice to the study which relied heavily on the narratives of the teachers, phenomenological method of research was used. Phenomenology entails a rich description of the significant experiences of the person experiencing the phenomenon. Each chapter in the dissertation showed the underpinning dimensions in the narratives of the teachers. In the Three Storytellers, the lives of three teachers with different levels of commitment were discussed. Their stories showed that the social environment can: 1) change teacher’s perception about teaching; 2) heighten or diminish teachers’ commitment to teaching. On the other hand, chapter five illustrates the effect of poverty on the teachers’ attitude towards their students. The students became the teachers’ mentor on the reality of life. Power is a recurring theme in the stories of the teachers. The different social groups in school possessed hidden powers which are manifested in the daily activities of the teachers. Salient among the findings is that students unwittingly have power over their teachers. Likewise, teachers have power over their superiors particularly the principal. The synthesis of the stories of the teachers highlighted the following socio-cultural dimensions of education: (1) the choice of teaching as a profession is a matter of convenience; (2) there is a tension between commitment and sustenance; (3) poverty impairs students’ participation in education; (4) teachers’ are unprepared to handle the student’s life crisis; (5) teachers are predisposed to impose discipline to their students; (6) teachers are agents of manipulation; and (7) teachers are victims of manipulations..." --
Dissertation
Keywords: Teachers -- Philippines -- Manila Metropolitan Area -- Biography; Teachers -- Philippines -- Manila Metropolitan Area -- Social conditions; Teachers -- In-serice training -- Philippines -- Manila Metropolitan Area